Improving energy efficiency of distillation using heat pump assisted columns. Issue 6 (4th September 2014) - Reddy, C. C. S.; Fang, Y.; Rangaiah, G. P.
ABSTRACT Distillation is a widely used separation technique in process industries, although it requires substantial energy inputs. In this study on improving the energy efficiency, both compression and absorption type heat pumps along with feed preheat are analyzed for two common distillation processes of a typical petroleum refinery, to recover waste heat at lower temperatures by upgrading it to useful temperature levels. The heat pumps are also coupled with intermediate heat exchangers (HEXs) to improve cost savings further. The case studies in this investigation are sour water stripper and the C4 separation unit consisting of a deisobutanizer and debutanizer; these include distillation with a partial condenser and separation of compounds having wide boiling points, which have not been studied earlier. Results from these case studies indicate that heat pumps can generally achieve attractive cost savings and that further addition of intermediate HEXs usually worsens the payback, mainly due to additional capital cost. However, intermediate HEXs are beneficial for cases where heat pump application between condenser and reboiler is not economical or feasible, especially in the case of distillation operations requiring very high temperature lifts. © 2014 Curtin University of Technology and John Wiley & Sons, Ltd.